Geographic Thinking in School Teaching and Learning - Souto González, Xosé Manuel (Boletín de Estudios Geográficos, 2024)
Geographic thinking is a form of knowledge that allows us to convincingly explain social problems that have a territorial context. However, in the school environment, if necessary it is not enough. We need to know how to learn this specific knowledge from people and understand how images and memories of similar problems are introduced into their mental schemas to influence their decisions through the practical sense of their decisions. Knowing how to reach geographic thinking in middle school and what its implications are for the praxis of the objectives of this article.